An Overview and Membership Process of PIC/S and ICH and its Requirement for Global Regulatory Harmonization of Drugs - Mahajan, Purvika; Thakkar, Arti (Current Drug Therapy, 2024)
Due to the increased globalization of regulatory authorities, it has become important to enhance harmonization efforts in creating regulatory requirements, checking and determining GMP compliance, licensing production locations, recalling defective batches, and boosting information interchange. ICH and PIC/S are the international platforms that provide an appealing and stable framework for addressing such globalization concerns. A country having a membership of PIC/S or ICH gives an assurance of the quality, safety, and efficacy of their medical products exported across the globe. Joining such international platforms helps the Pharmaceutical Industries and Regulatory System of that country to improve quality standards. In the present study, the main objective is to gain knowledge regarding the procedures to obtain membership in international platforms such as ICH and PIC/S, and to know the changes/modifications that needs to be done at the institutional/organizational level before applying for the membership, also, to gain knowledge of the eligibility criteria for the application and to know the differences in regulatory guidance in GMP aspects of different regulatory authorities. By joining these international platforms, ICH and PIC/S, non-member countries will be able to tap into the potential for pharmaceutical exports, especially in the largest countries of the globe. After joining these international platforms, the semi or low-regulated nations’ pharmaceutical industries will be benefited greatly in terms of cost savings, export convenience, and most importantly, market access. Membership in ICH and PIC/S will be able to provide the semi or low-regulated Drug Regulatory Authority a global footprint and give foreign regulatory agencies confidence in semi or low-regulated regulatory agencies.
Keywords: good manufacturing practice